The design and study of a vapor chamber fabricated via laser powder bed fusion - Bailey, Christopher M. (Kansas State University, 2022)
Laser Powder Bed Fusion (LPBF) was utilized to create aluminum alloy (i.e., AlSi10Mg) specimens for two related sets of experiments for this study. The first was a series of 5-mm-diameter support pillars with a fixed height of 5 mm containing varying filet angles and build orientations (i.e., 0˚, 10˚, 20˚, 30˚, 40˚, 50˚, and 60˚ from the normal surface) to determine their effects on surface roughness and water wettability. From experiments, anisotropic wetting was observed due in part to the surface heterogeneity created by the LPBF process. The powder-sourced AlSi10Mg alloy, typically hydrophobic, exhibited primarily hydrophilic behavior for build angles of 0˚ and 60˚, a mix of hydrophobic and hydrophilic behavior at build angles of 10˚ and 20˚, and hydrophobic behavior at 30˚, 40˚, and 50˚ build angles. Measured surface roughness, Ra, ranged from 5-36 µm and varied based on location. Build angles of 30˚ and 40˚ provided for the smoothest surfaces. A significantly rougher surface was found for the 50º build angle. This abnormally high roughness is attributed to the melt pool contact angle having maximal capillarity with the surrounding powder bed. Based on the wetting and roughness data from the support pillars a 100 x 100 x 10mm vapor chamber (VC) was created at a 45˚ printing orientation from the normal surface to provide a proof of concept for the additive manufacturing (AM) of multiphase heat spreaders and its corresponding thermal conductivity. From production, it was found possible to manufacture and successfully inject an AM VC with deionized and degassed water as a working fluid. From experiments, the results were inconclusive to successfully determine a thermal conductivity; however, the critical temperature conditions necessary to begin multiphase thermal dissipation were observed.
Keywords: Additive manufacturing; Laser powder bed fusion; Phase change heat spreader; Heat transfer; High thermal conductivity